UPAYA PENINGKATAN KOMPETENSI BAHASA INGGRIS BAGI GURU MADRASAH IBTIDAIYAH AL-FATAH BANJARNEGARA MELALUI PROGRAM PELATIHAN BASIC ENGLISH - Ganjarjati, Nur Innayah (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
This study aims to explore the improvement of English language competence, especially for teachers of Madrasah Ibtidaiyah (MI) Al-Fatah Banjarnegara through a basic English training program that includes Speaking, Reading, Listening and Writing. The method used is descriptive qualitative, namely by interview and observation approaches to ten (10) MI Al Fatah Banjarnegara Class teachers who participated in the training. This study measures the level of English language ability before and after training. This measurement is carried out through tests before and after training or pre and post tests. Observation data during training, interviews and scores before and after training were then analyzed and their meanings sought. The results of the study indicate that basic English training helps improve teachers' English skills, especially in these four basic English which are able to improve speaking, reading, listening and writing skills in teaching English. Factors such as teacher motivation and institutional support influence the success of the training. This study recommends the implementation of ongoing training programs and the provision of training modules according to needs.